Cytochrome b5: A versatile electron carrier and regulator for plant metabolism - Liu, Chang-Jun (Frontiers in Plant Science, 2022)
Cytochrome b5 (CB5) is a small heme-binding protein, known as an electron donor delivering reducing power to the terminal enzymes involved in oxidative reactions. In plants, the CB5 protein family is substantially expanded both in their isoform numbers and their cellular functions, compared to their yeast and mammalian counterparts. As an electron carrier, plant CB5 proteins function not only in fatty acid desaturation, hydroxylation and elongation, but also in the formation of specialized metabolites such as flavonoids, phenolic esters, and heteropolymer lignin. Furthermore, plant CB5s are found to interact with different non-catalytic proteins such as ethylene signaling regulator, cell death inhibitor, and sugar transporter, implicating their versatile regulatory roles in coordinating different metabolic and cellular processes, presumably in respect to the cellular redox status and/or carbon availability. Compared to the ample studies on biochemistry and cellular functions of mammalian CB5 proteins, the cellular and metabolic roles of plant CB5 proteins have received less attention. This article overviews the fragmentary discoveries and information pertaining to the plant CB5 proteins, and discusses the conventional and peculiar functions that plant CB5s might play in different metabolic and cellular processes. Gaining comprehensive insight into the biological functions of CB5 proteins could offer effective biotechnological solutions for tailoring plant chemodiversity and cellular responses to environment stimuli.